2016
DOI: 10.1007/s00223-016-0117-7
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-Related Protein 5 Attenuates High Phosphate-Induced Calcification in Vascular Smooth Muscle Cells by Inhibiting the Wnt/ß-Catenin Pathway

Abstract: Vascular calcification (VC) is highly prevalent and represents a major cardiovascular risk factor in chronic kidney disease (CKD) patients. High phosphate (HP) levels are strongly associated with VC in this population. Secreted frizzled-related protein 5 (SFRP5), one of the inhibitors of the Wnt pathway, is a known anti-inflammatory adipokine with a positive effect on metabolic and cardiovascular diseases, in addition to its anticancer potency. However, the role of SFRP5 in the pathophysiology of VC is unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
1
29
2
Order By: Relevance
“…Our study indicated that Wnt pathway was involved in CKD VC, which is consistent with previous studies . Addition of Wnt pathway inhibitor secreted frizzeled‐related protein 5 could inhibit high phosphate‐induced calcification of VSMCs .…”
Section: Disccusionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study indicated that Wnt pathway was involved in CKD VC, which is consistent with previous studies . Addition of Wnt pathway inhibitor secreted frizzeled‐related protein 5 could inhibit high phosphate‐induced calcification of VSMCs .…”
Section: Disccusionsupporting
confidence: 92%
“…These two factors are both involved in canonical Wnt pathway. Several other canonical Wnt pathway factors including Wnt8b and Frizzled‐related protein have also been suggested to play roles in phosphate‐induced calcification in VSMC . However, Wnt5a, a non‐canonical Wnt pathway factor, was not significantly associated with VC in our study.…”
Section: Disccusioncontrasting
confidence: 80%
“…The link between SFRP5 and renal function has not been investigated in detail yet. One study reported that SFRP5 inhibited high phosphate-induced calcification of vascular smooth muscle cells which is a major cardiovascular risk factor in chronic kidney disease (CKD) [30]. However, another study showed that the Sfrp5 gene is hypermethylated and downregulated in a mouse model of CKD, whereas injection of recombinant Sfrp5 inhibited Wnt signaling and attenuated renal fibrosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BMP‐9 was also been reported to induce VC through activating the Wnt/β‐catenin pathway . In contrast, Deng et al revealed secreted frizzled‐related protein 5 (SFRP5) attenuates high phosphate‐induced calcification in vascular smooth muscle cells by inhibiting the Wnt/β‐catenin pathway . Thus, Wnt/β‐catenin pathway was generally identified as an inducer of vascular calcification, and regulated by several signal molecules, including BMP family and SFRP5.…”
Section: Discussionmentioning
confidence: 99%